Healthusiasme : making costumers healthy and happy - Jauquet, Christophe, ....- (Tielt : LannooCampus, 2019)
Why are people more conscious of their health today than ever before? How can you truly make your customers healthy and happy? What do health-conscious people expect from your company or brand? In a world where technology increasingly meets our basic and social needs, people want to become the best version of themselves. A major aspect of this is that we aspire to be(come) as healthy and happy as possible. Healthusiasm not only describes the enthusiasm to live healthily and happily, but also explains what people expect from products, services and experiences in their quest for selfactualisation. The book challenges companies and brands to think about how they can help their customers in their aspiration.